(untitled) (Journal on studies and research of academic knowledge, 2017)
The mango is a tropical fruit that is abundant in Paraguay, especially in summer. The fruit is not exploited industrially, despite its many uses. The main product is the pulp, peel and seed as by-products with potential applications. In this paper, the proximal composition (oil, protein, carbohydrates, moisture and ash) of mango seeds (Mangifera Indica L) of the varieties Tommy Atkins and criolla, with a focus on the oil content was evaluated. According to literature, mango oil could be a substitute for cocoa butter in chocolate production. Results showed 13% and 12% of oil, 6.54% and 5.41% of proteins, 34% and 32% of carbohydrates and 43.5% and 45.8% of moisture percentages for var Tommy Atkins and criolla. Thus, it can be concluded that the oil content is high and could be used in industry as an important ingredient to be incorporated to differenet products.